2003
DOI: 10.2337/diabetes.52.5.1292
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in the Human Winged Helix/Forkhead Transcription Factor Gene FOXC2 in Pima Indians

Abstract: FOXC2 is a winged helix gene that has been shown to counteract obesity, hypertriglyceridemia, and diet-induced insulin resistance in rodents. Therefore, FOXC2 was analyzed as a candidate gene for susceptibility to type 2 diabetes in Pima Indians. Four variants were identified by sequencing the coding region, as well as 638 bp of the 5 region and 300 bp of the 3 region of the gene. Two single nucleotide polymorphisms (SNPs) were found in the putative promoter region, a C-512T transition and a G-350T. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
35
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 9 publications
6
35
1
Order By: Relevance
“…7 The T/T genotype of a common polymorphism in the 5 0 untranslated region (5 0 UTR) of the gene (À512C4T) has been associated with increased mRNA expression in visceral compared to subcutaneous fat, and the T-allele with higher insulin sensitivity and lower triglyceride levels. 7,8 Although these data identified FOXC2 as a candidate gene for insulin resistance and/or type 2 diabetes, three recent reports in Japanese, Pima Indians and Danish Caucasians have failed to identify an association between FOXC2 and type 2 diabetes. [8][9][10] In addition, contrasting with previous data, the Tallele was weakly associated with increased waist-to-hip ratio (WHR), plasma triglycerides and measures of insulin resistance in the Danish study.…”
Section: Introductionmentioning
confidence: 99%
“…7 The T/T genotype of a common polymorphism in the 5 0 untranslated region (5 0 UTR) of the gene (À512C4T) has been associated with increased mRNA expression in visceral compared to subcutaneous fat, and the T-allele with higher insulin sensitivity and lower triglyceride levels. 7,8 Although these data identified FOXC2 as a candidate gene for insulin resistance and/or type 2 diabetes, three recent reports in Japanese, Pima Indians and Danish Caucasians have failed to identify an association between FOXC2 and type 2 diabetes. [8][9][10] In addition, contrasting with previous data, the Tallele was weakly associated with increased waist-to-hip ratio (WHR), plasma triglycerides and measures of insulin resistance in the Danish study.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting, however, that in this paper the carriers of the T-allele had a somewhat higher WHR and this variable was not included in the multivariate regression analysis. Although the WHR difference was not quite significant, it may have contributed to the borderline In addition, it should be mentioned that other studies have found just the opposite, namely an association of the T-allele with enhanced insulin sensitivity [3] and lower plasma triglycerides [2,3]. To detect a 10% difference between genotypes, the statistical power of our data set was more than 80% for the relevant parameters tested.…”
mentioning
confidence: 63%
“…Since a previous study [2] found a sex-specific effect on triglycerides, we performed the analysis in men and women separately, but also found no significant association with the −512 genotype. In particular, no associations with plasma insulin, C-peptide or serum triglycerides were observed.…”
Section: Letters 757mentioning
confidence: 99%
See 2 more Smart Citations